Peran Ekonomi Kreatif Dalam Peningkatan Perekonomian Pengrajin Tali Tenun Persepektif Ekonomi Islam - Eviatun, Esti; Hasan, Saukani; Sari, Romida Rifiana (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Creative economy is a concept in the new economic era that allows communities to start businesses and channel their innovative ideas to create something new and different. This research aims to understand the role of the creative economy in increasing the income of woven rope artisans in Kalianda, viewed from the perspective of Islamic economics. This is a qualitative study that employs a descriptive approach. This research finds that making woven ropes is very difficult, and the wages earned differ from the weaving ropes process. However, poverty keeps the artisans engaged in weaving rope work. As observed, most woven rope artisans in Kalianda still rely on their income from crafting woven ropes to make a living. These craftsmen are reluctant to remain idle and dependent on others; they work enthusiastically to meet their livelihood needs. Keywords : Creative economy, Income, Islamic economics.